Analisis Maqoshid Syariah terhadap Penerapan Akad Muzaroah dan Ijarah Pada Petani Cabe Nagarri Taeh Baruah - Deni Putra, Muhammad; Ismail, Dailani; Alimin, Alimin; Fahlefi, Rizal; Fadilla, Siti (ILTIZAM Journal of Shariah Economics Research, 2023)
Regarding the development of agricultural land management, the muzāra'ah contract scheme is considered the most suitable and fair contract, and in accordance with sharia principles. However, in its implementation, many problems arise between sharecroppers and land owners. From the initial survey that the author conducted with Basril, one of the chili farmers in Taeh Baruah Village, it was found that sharing the results of the land, especially in chili farming, tends to cause disharmony in social interactions due to because sharecroppers are not professional, transparency is weak. Based on this phenomenon, the author conducted an in-depth study regarding benchmarks for the benefits of muzāra'ah and ijārah contracts in agricultural land management using the Maqasid Syariah approach. From the measurement results, it was found that currently in Nagari Taeh Baruah, the use of an ijārah contract in terms of agricultural land cooperation is the most beneficial contract compared to the muzāra'ah contract. This is due to the community's habit of carrying out cooperation in the agricultural sector only verbally, and the level of honesty of some farmers is still low, which tends to result in social disharmony among chili farmers in Nagari Taeh Baruah.